Effect of Ethanol-water Concentration as Extraction Solvent on Antioxidant Activity of Acalypha indica - Fadhila, Salma Iza; Hayati, Elok Kamilah; Rafi, Mohamad; Sabarudin, Akhmad (al Kimiya: Jurnal Ilmu Kimia dan Terapan, 2023)
Acalypha indica is an abundant and obtainable wild weed plant in Indonesia. This is a possible opportunity to enhance its utility. The effect of free radicals is one of the factors that contribute to oxidative stress in the body, which can lead to cell damage and trigger various diseases. Plants rich in antioxidants can inhibit free radical reactions and protect the body from oxidative stress. In this study, we conducted the identification of major metabolite compounds using UHPLC-Q-Orbitrap HRMS from 70% ethanol extracts of Acalypha indica. We also performed phytochemical and antioxidant activity tests with various concentrations of ethanol-water solvents including water, 30%, 50%, 70% ethanol, and absolute ethanol to determine the optimal extraction conditions and the influence of solvent concentration on the antioxidant activity of Acalypha indica extract. The results of UHPLC-Q-Orbitrap HRMS identification showed that the 70% ethanol extract of Acalypha indica contains 10 major compounds suspected to correlate with its antioxidant activity. These include five flavonoids compounds (palasitrin, vitexin 2"-o-p-coumarate, isorhamnetin 3- (3",6"-di-p-coumarylglucoside), peucenin, and sulfuretin), two amino acid compounds (2-amino-3-carboxymuconic acid semialdehyde and N-Acetyl-L-phenylalanine), two carboxylic acid compound (citric acid and traumatic acid), and one phenolic compound (quinic acid). Phytochemical tests show positive results for flavonoids, tannins, alkaloids, and triterpenoids in each of water, 30%, 50%, 70% ethanol, and absolute ethanol extracts. The best antioxidant activity was obtained from the 70% ethanol extract with an IC50 value of 47.064 ppm, categorizing it as an extremely strong antioxidant.